(untitled) (Scientific journal of the Fergana State University, 2023)
In the article, we set the task to study the waters and their microflora of the Chimkurgan and Pachkamar reservoirs, existing in the Kashkadarya region and intended for human consumption and irrigation of arable land. As the main object of our research, samples were taken from the coastal part of the reservoirs and 300-400 meters from the coast at a depth of 10-15 cm above the water level. The results of the study showed that the number of microorganisms is not the same throughout the year and depending on the season, i.e. the number of microorganisms is higher than in other seasons, especially in summer and autumn.